Urbanization, Agglomeration, and Economic Development - Quigley, John M. (World Bank, Washington, DC, 2017)
This paper reviews the linkages between urbanization and economic development. It articulates the relationship between urban density and potential increases in productivity, through specialization, complementarities in production, through the diffusion of knowledge and mimicry, and simply through size and scale. The factors limiting the efficient sizes of cities are analyzed. The paper reviews empirical knowledge, from underdeveloped countries as well as high-income industrial societies, about the importance and magnitudes of these productivity gains. The analysis documents the close link between gains in economic efficiency and the urbanization of populations in most parts of the world.